Role of Spin-Orbit Coupling and Hybridization Effects in the Electronic Structure of Ultrathin Bi Films - Hirahara, T.; Nagao, T.; Matsuda, I.; Bihlmayer, G.; Chulkov, E. V.; Koroteev, Yu. M.; Echenique, P. M.; Saito, M.; Hasegawa, S. (Physical review letters, 2006)
The electronic structure of Bi(001) ultrathin films (thickness > or =7 bilayers) on Si(111)-7x7 was studied by angle-resolved photoemission spectroscopy and first-principles calculations. In contrast with the semimetallic nature of bulk Bi, both the experiment and theory demonstrate the metallic character of the films with the Fermi surface formed by spin-orbit-split surface states (SSs) showing little thickness dependence. Below the Fermi level, we clearly detected quantum well states (QWSs) at the M point, which were surprisingly found to be non-spin-orbit split; the films are "electronically symmetric" despite the obvious structural nonequivalence of the top and bottom interfaces. We found that the SSs hybridize with the QWSs near M and lose their spin-orbit-split character.